The transfer of the Austrian dual system of vocational education to transition and developing countries: An analysis from a developmental perspective - Margarita Langthaler (Austrian Foundation for Development Research (ÖFSE), 2015)
The increasing international interest in the Austrian dual system of apprenticeship has triggered a trend to transfer this system, or parts of it, to foreign countries including developing and transition countries. This paper analyzes the trend from a developmental perspective. After a historic outline of vocational education in international development and the discussion of current global trends in vocational education, the paper elaborates on the transfer of the dual system from a theoretical as well as an empirical perspective. It then goes on to describe the Austrian dual system of apprenticeship. In the empirical part, the paper first examines the status quo of the transfer trend as well as key players, funding possibilities, approaches, lessons of experience and challenges. Findings are subsequently analyzed from a developmental perspective. Finally, recommendations are made of how to strengthen the developmental impact. The paper concludes that while current transfer activities respond well to several criteria set out by the Austrian Development Cooperation, a number of open questions remain as to sustainability, systemic effect and economic bias, among others.
Keywords: 330; Vocational Education and Training; Dual System of Apprenticeship